STUDI EVALUASI TAMAN LINGKUNGAN DI KOTA MALANG - Budiyono, Debora; Kurniawan, Hendra (BUANA SAINS, 2025)
An Environmental Park is an urban green open space that plays a crucial ecological, social, and aesthetic role. However, several established environmental parks in Malang City, namely Merjosari, Slamet, Merbabu Family, and Trunojoyo Parks, are experiencing a decline in visitors. This decline is attributed to a lack of functional optimization and aesthetic appeal, compounded by competition from newer parks. This research aims to evaluate the functional performance of these specific parks. The study employs the Key Performance Index (KPI) methodology to assess key aspects, including physical conditions, park quality, spatial design, park elements, and visitor activities. The results indicate that only Merjosari Park meets the standard criteria. Otherwise, Slamet Park, Merbabu Family Park, and Trunojoyo Park were categorized as below standard. These findings highlight the urgent need for the Malang City Environmental Agency, as the managing authority, to implement comprehensive improvements. Recommendations focus on enhancing the parks' physical components, quality, spatial layout, and amenities to revitalize their function and better serve the community.